Dermoscopic hemorrhagic dots: an early predictor of response of psoriasis to biologic agents - Aimilios Lallas; Giuseppe Argenziano; Iris Zalaudek; Zoe Apalla; Marco Ardigo; Patricia Chellini; Natalia Cordeiro; Mariana Guimaraes; Athanassios Kyrgidis; Elizabeth Lazaridou; Caterina Longo; Elvira Moscarella; et al. (Mattioli1885, 2016)
Background: Biologic agents are routinely used in the treatment of severe psoriasis. The evaluation of treatment response is mainly based on the physician's global clinical assessment. Objective: To investigate whether dermoscopy might enhance the assessment of response of psoriasis to treatment with biologic agents. Methods: Patients with severe psoriasis scheduled to receive a biologic agent were enrolled in the study. A target lesion from each patient was clinically and dermoscopically documented at baseline and after one, two and six months. The clinical response was evaluated by the recruiting clinicians at all visits, while dermoscopic images were evaluated by two independent investigators, blinded to the clinical information. Chi Square test was used for cross-tabulation comparisons, while odds ratios, 95% confidence intervals and p values were calculated using univariate logistic regression. Results: Overall, there was a significant correlation between clinical response and vessel distribution at all time points: a regular vessel distribution correlated with no response, a clustered distribution with partial response, and the dermoscopic absence of vessels with complete response. The presence of dermoscopic hemorrhagic dots was a potent predictor of favorable clinical response at the subsequent visit at all time points. Among lesions initially clinically responding and later recurring, 87.5% displayed dermoscopic dotted vessels despite the macroscopic remission. Conclusion: Dermoscopy might be a useful additional tool for evaluating the response of psoriatic patients to biologic agents. Hemorrhagic dots represent an early predictor of clinical response, while the persistence or reappearance of dotted vessels might predict clinical persistence or recurrence, respectively.